Clinical Features of Primary Vein Grafts in Free Tissue Transfers. (12th March 2015) - Nemoto, Mitsuru; Kumazawa, Kenichi; Uchinuma, Eiju; Kounoike, Natsuko; Takeda, Akira
Abstract : The outcomes of free tissue transfers combined with vein grafts have been inconsistent, and discussions continue regarding their appropriate use. Of the 142 free tissue transfers that we performed from January 2004 to December 2011, we retrospectively analyzed 15 consecutive patients who underwent free tissue transfers in combination with vein grafts. Etiologies included trauma (8 patients), infection (4), and tumor (3). Types of free tissue transfers were fibula (4), anterolateral thigh (3), groin (3), jejunum (3), latissimus dorsi (1), and dorsal pedis (1). Vein grafts were used for the artery (6), vein (2), or both (7). The donor veins were the saphenous vein (12) and the external jugular vein (3). The mean length of the grafted veins was 10.8 cm (range: 4–18 cm). Even though complications of congestion occurred in 2 patients, these flaps survived by reexploration. The flap success rate was 15 of 15 (100%) of vein grafted free flaps versus 124 of 127 (97.6%) of free flaps not requiring vein grafts. To improve the success rate of free tissue transfers combined with vein grafts, securing healthy recipient vessels, meticulous surgical handling, a reliable vascular anastomosis technique, and strict postoperative monitoring are crucial.